The Key to Managing Staff Training: A Learning Management System. - Geiman, Diane (Corrections Today)
The article discusses the use of learning management system (LMS) software in corrections staff training. LMS focuses on initial knowledge and skills acquisition, continuing education, refresher learning, and competency upgrading. Topics include choosing an effective LMS vendor, the benefits and costs of building an in-house LMS, and the Corrections Online Training Collaborative (COTC) LMS offered by the American Correctional Association (ACA).